Parasites of wild and captive Nene Branta sandvicensis in Hawaii - Bailey, Tom; Black, Jeffrey (Wildfowl, 1995)
The risk of introducing disease or parasites into the wild has long concerned managers involved in the Nene recovery programme. In this initial survey helminth eggs were found in samples from 17 of 77 free-ranging Nene and eight of 28 captive Nene, giving an overall prevalence of 22%. Percent prevalence, estimated for each of the nine collection sites, was not correlated with bird density. No haemoparasites were detected on microscopic examination of the blood smears. A longer term study to determine the dynamics of the Nene-parasite relationship is needed to confirm the initial suggestion that the birds’ recovery probably is not limited by heavy parasite infection.